Exploring The Influence of The KoPI Lokal Islami Learning Model and Gender on 21st-Century Skills in Islamic Elementary Schools - Kurniawan Arizona; G. Gunawan; Ahmad Harjono; Joni Rokhmat; Agus Ramdani; Aa Sukarso; Ida Kaniawati (Jurnal Pendidikan Islam, 2025)
This study aimed to determine the influence of the KoPI Lokal Islami (KLI) learning model, gender, and their interaction on 21st-century skills. This study used an experimental method through a factorial design. The study involved 174 students from Islamic elementary schools, divided into three treatment groups: 58 students in the KLI model, 58 in the cooperative learning (CL) model, and 58 in the direct instruction (DI) model. Among the participants, 88 were male, and 86 were female. Data were collected through tests, observation sheets, and questionnaires, all of which were validated by experts. Data analysis was conducted using a two-way ANOVA, followed by Tukey HSD and LSD tests, after normality and homogeneity tests were performed. The results showed that the KLI model significantly improved 21st-century skills (p=0.000) by creating a more contextual and meaningful learning experience. Significant differences were also found between male and female learners (p=0.039), with females, in general, being more focused on developing 21st-century skills at primary school age. The interaction between model and gender is not significant (p=0.799), indicating that these two factors influence 21st-century skills independently. This research makes an essential contribution to the design of learning models that are more relevant to current demands and can serve as a basis for educational policy recommendations in Islamic primary schools.